THE EFFECTIVENESS OF USING MYENGLISHSTEP AND SUMBER.BELAJAR.KEMDIKBUD.GO.ID IN COMPOSING DESCRIPTIVE - Amin Wibowo (Universitas PGRI Semarang, 2022)
This study investigates how effective using myenglishstep and sumber.belajar.kemdikbud.go.id 7th grade students in composing descriptive text at SMP Negeri 42 Semarang. The writer used a quantitative method. There 2 as experimental classes which is using myenglishstep and sumber.belajar.kemdikbud.go.id. The result of the study is that there is correlation between myenglishstep and sumber.belajar.kemdikbud.go.id in composing descriptive text for 7th grade students.The objective is to discover which show is more viable than the two models when connected in learning to compose descriptive writings in course 7 junior high school. Based on the calculation of the normal increment, the student's last test normal score in the test course 1 of 87.230, where's the normal esteem of the student's last test in the test course 2 of 80.50. There's a distinction in esteem of 6.73 between experimental lesson 1 and exploratory lesson 2. So, it can be concluded that class Experiment 1 is more successful than test course 2.On the other hand, It can be seen that the normal beginning test score was 79,961 and the normal last test score was 87,230. This appears that the utilize of myenglishstep demonstrate is viable when connected to learning compose an informative content since the comes about appear an increment between some time recently and after the exploratory lesson 1 was given a treatment of 7.269.